The Organization and Connections of Second Somatosensory Cortex in the Agouti - Santiago, Lucidia F.; Freire, Marco Aurelio M.; Picanço-Diniz, Cristovam W.; Franca, João G.; Pereira, Antonio (Frontiers in Neuroanatomy, 2019)
In order to understand how the mammalian sensory cortex has been structured during evolution, it is necessary to compare data from different species across distinct mammalian lineages. Here, we investigated the organization of the secondary somatosensory area (S2) in the agouti (Dasyprocta aguti), a medium-sized Amazonian rodent, using microelectrode mapping techniques and neurotracer injections. The results of electrophysiological recordings were correlated with both cytochrome oxidase (CO) histochemistry and with patterns of corticocortical connections in tangential sections. The electrophysiological mapping of the lateral strip of parietal cortex adjacent to the primary somatosensory area (S1) revealed that S2 displays a mirror-reversed topographical representation of S1, but with a smaller cortical magnification factor. The caudal border of S2 is surrounded by sensory fields which also respond to auditory stimulation. BDA injections into the forelimb representation of S2 revealed a dense homotopic ipsilateral projection to S1, supplemented by a less dense projection to the caudolateral cortex located near the rhinal sulcus (parietal rhinal area) and to a frontal region probably associated with the motor cortex. Our findings were similar to those described in other mammalian species, reinforcing the existence of a common plan of organization for S2 in the mammalian parietal cortex